2008
DOI: 10.1080/17290376.2008.9724921
|View full text |Cite
|
Sign up to set email alerts
|

Private pharmacies in an integrated approach to HIV/AIDS services

Abstract: João Carapinha (BPharm, MM P&DM) is the owner of PharmaLogica, a consulting company active in South Africa and the USA. Its aim is to respond with effective and innovative insight to the needs of the pharmaceutical sector in developing countries. PharmaLogica has worked for non-profit institutions, government agencies and also consulted on a project basis for pharmaceutical companies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Due to this disappointing reality, it has been suggested that the best way to utilise community pharmacists in the management of HIV/AIDS is by building an integrated approach to HIV/AIDS services that will be based on 'task sharing' instead of just 'task shifting' , public-private partnerships, HIV/AIDS Resource centres in pharmacies and focus on ART. [12,22] Regardless of the creative ideas offered and the somewhat theoretical willingness of all official stakeholders, based on the latest Human Resources for Health document which focuses on the Strategy for the Health Sector 2012/13-2016/17, as well as the realities on the ground as reflected in the 2010 interviews, it seems that 'pharmacists have been left out of the loop' as articulated by one of the pharmacists interviewed in the 2010. [40,41] Indeed, the reality on the ground is that of a missed opportunity as the pharmacists have not risen to the challenge and they remain on the margins, and not at the centre, of those professionals managing HIV/AIDS in SA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this disappointing reality, it has been suggested that the best way to utilise community pharmacists in the management of HIV/AIDS is by building an integrated approach to HIV/AIDS services that will be based on 'task sharing' instead of just 'task shifting' , public-private partnerships, HIV/AIDS Resource centres in pharmacies and focus on ART. [12,22] Regardless of the creative ideas offered and the somewhat theoretical willingness of all official stakeholders, based on the latest Human Resources for Health document which focuses on the Strategy for the Health Sector 2012/13-2016/17, as well as the realities on the ground as reflected in the 2010 interviews, it seems that 'pharmacists have been left out of the loop' as articulated by one of the pharmacists interviewed in the 2010. [40,41] Indeed, the reality on the ground is that of a missed opportunity as the pharmacists have not risen to the challenge and they remain on the margins, and not at the centre, of those professionals managing HIV/AIDS in SA.…”
Section: Resultsmentioning
confidence: 99%
“…There is undoubtedly potential for community pharmacists to be involved in the prevention and treatment of HIV/AIDS in its various stages. [22][23][24] Of relevance to the potential role of the pharmacist in the various facets of the epidemic is the fact that people who are infected with HIV lead relatively healthy and productive lives for many years after they are infected. Although life can be prolonged with ART, as there is as yet no cure, the treatment needs and demands are ongoing.…”
Section: The Potential Role Of Community Pharmacistsmentioning
confidence: 99%